Exergaming in youth: Effects on physical and cognitive health - Best, J. R. (Zeitschrift für Psychologie, 2013)
Exergaming (a portmanteau of "exercise" and "gaming") is a relatively new genre of interactive video gaming that stimulates an active, whole-body gaming experience. Exergaming could have a significant positive impact on youth as across the globe youth are living more sedentary lifestyles. Exergaming has the potential to thwart this trend by engaging youth in physical activity (PA). Exergaming is not only physically-engaging but is also cognitively-engaging, and this combination of physical and cognitive engagement may translate into improved cognitive function in youth. The purpose of this review article is to examine the state-of-the-art in exergaming research to address whether exergames are a viable tool to promote PA in youth and benefit cognitive functioning among youth. The research addressing these questions is still quite nascent; therefore, only tentative conclusions can be drawn. However, this review points out promising lines of research and makes suggestions for future research to obtain more firm conclusions.